Prostaglandins and Their Receptors in Insect Biology - Stanley, David (Frontiers in Endocrinology, 2011)
We treat the biological significance of prostaglandins (PGs) and their known receptors in insect biology. PGs and related eicosanoids are oxygenated derivatives of arachidonic acid (AA) and two other C20 polyunsaturated fatty acids. PGs are mostly appreciated in the context of biomedicine, but a growing body of literature indicates the biological significance of these compounds extends throughout the animal kingdom, and possibly beyond. PGs act in several crucial areas of insect biology. In reproduction, a specific PG, PGE2, releases oviposition behavior in most crickets and a few other insect species; PGs also mediate events in egg development in some species, which may represent all insects. PGs play major roles in modulating fluid secretion in Malpighian tubules, rectum and salivary glands, although, again, this has been studied in only a few insect species that may represent the Class. Insect immunity is a very complex defense system. PGs and other eicosanoids mediate a large number of immune reactions to infection and invasion. The actions of most PGs are mediated by specific receptors. Biomedical research has discovered a great deal of knowledge about PG receptors in mammals, including their structures, pharmacology, molecular biology and cellular locations. Studies of PG receptors in insects lag behind the biomedical background, however, recent results hold the promise of accelerated research in this area. A PG receptor has been identified in a class of lepidopteran hemocytes and experimentally linked to the release of prophenoloxidase. We conclude that research into PGs and their receptors in insects will lead to important advances in our understanding of insect biology.